Impact of Upgrade Programmes on the Competitiveness: Case of the Algerian Companies - Ghomari, Souhila (Economics and Business, 2020)
Faced to a socio-economic environment that is marked by globalization of trade and competitiveness, Algeria is committed, like its neighbours, to do upgrade programmes which aim to support the dynamic of restructuring process, the industrial integration and growth. The strategic goal is to upgrade to the requirements of the free trade to take advantage of the positive effects of liberalization and strengthen the production capacity, sales and export. This general target will lead the Algerian companies to achieve two ambitions: to become competitive in price / quality, innovation, and to be able to survive and control the evolution of the technology and the markets. Achieving these ambitions requests from the Algerian companies a major effort, i.e., to adapt and change their organisational methods and practices, especially in technology, innovation, cost control and quality supervision, training, products and markets, sales policies, management, openness to technical and commercial partners. The present paper describes the impact of upgrade programmes on the competitiveness of Algerian companies. For this reason, a model has been developed that analyses the competitiveness of a company across several dimensions (commercial, financial, technical, human, as well as social & managerial). To process the data collected in the survey, an exploratory factor analysis, confirmatory analysis and structural equation methods have been used. The results of the research have confirmed the main hypothesis that upgrading has a positive impact on the overall competitiveness of companies that have initiated and finalised an upgrade programme.